Kajian Etnolinguistik Istilah Makanan dan Jajanan Tradisional dalam Tradisi Tingkeban di Jombang - Taufiq Hidayat; Taswirul Afkar; Misbahul Khanif; Mukhammad Aqmal Aziz (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
Indonesia as a multicultural country has various traditions that reflect social and spiritual values, one of which is the tingkeban tradition in Javanese culture. This tradition is not only a spiritual ritual for the safety of pregnant women and their fetuses, but also a medium for cultural expression through the symbolism of traditional food. This study aims to identify the terms of traditional food and snacks in the tingkeban ceremony and explore the symbolic and cultural meanings contained therein through an ethnolinguistic approach. The focus of the study was directed at the people of Ketapangkuning Village, Ngusikan District, Jombang Regency, East Java, who still maintain the traditional tingkeban practice. By using an ethnolinguistic approach, this study attempts to trace the relationship between language and culture reflected in the lexicon of traditional food as a representation of the values of harmony, balance, and respect for life in Javanese society.